Response of coriander (Coriandrum sativum L.) foliage to different rates and methods of nitrogen application (Bangladesh Journal of Agricultural Research, 2014)
The experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during January 2009 to February 2009 taking two coriander (Coriandrum sativum L.) lines, CS001 and CS003 to determine the nitrogen requirement of coriander foliage crop and to select the best method of nitrogen application for maximizing foliage yield. The experiment was laid out in randomized complete block design with three replications having five nitrogen doses (0, 20, 40, 60, and 80 kg/ha) and four methods of N application (entire N dose as basal, ½ N as basal, and ½ N at 30 days after sowing as top dressing, ½ N as basal and ½ N at 30 DAS as foliar spray and 2/3 N at 20 DAS, 1/3 N at 30 DAS, and 1/3 N at 40 DAS as foliar spray). The nitrogen dose of 80 kg/ha and ½ N as basal and ½ N at 30 days after sowing as top dressing independently gave the maximum plant height, number of leaves/plant, single plant weight, plant weight/m2, and foliage yield/ha. Nitrogen @ 80 kg/ha applied half as basal and half at 30 DAS as top dress produced maximum foliage yield/ha closely followed by 60 kg and 40 kg N/ha with the same application method. The highest gross margin was recorded from 80 kg N/ha applied half as basal and half at 30 DAS as top dress (Tk. 262.705 thousand/ha) followed by 60 kg N/ha with the same application method (Tk. 259.529 and Tk. 254.342 thousand/ha, respectively) and these two combinations also gave the highest benefit-cost ratio of 6.90 DOI: http://dx.doi.org/10.3329/bjar.v39i2.20445 Bangladesh J. Agril. Res. 39(2): 359-371, June 2014